ä½¿ç”¨å¡«å—æ¸¸æˆå¯¹åŸ¹å¾·å°å¦äº”å¹´çº§çš„å¦ç”ŸæŽŒæ¡æ±‰è¯è¯æ±‡èƒ½åŠ›çš„æœ‰æ•ˆæ€§ - Rezeki, Sri; Afrimonika, Yoanna; Veronica, Tjen (Universitas Tanjungpura, 2025)
The purpose of this study is to determine the effectiveness of the use of crossword puzzle on the ability to master Chinese vocabulary of 5th grade students of Bina Bhakti Elementary School, and to determine the response of 5th grade students of Bina Bhakti Elementary School to crossword puzzle. This research uses experimental method, test method with pre-test and post-test design, and questionnaire. Divided into two groups, namely class 5A as the control group and class 5B as the experimental group. The results showed that there was a significant difference between the experimental group and the control group, where the experimental group experienced a better increase in vocabulary mastery ability by 88.78% compared to the control group by 73.34%. From the results of the questionnaire analysis of students' responses to the use of crossword puzzle, it can be seen that the use of crossword puzzle can increase students enthusiasm for learning Chinese and can help students master and remember Chinese vocabulary. Overall, the questionnaire results obtained with an average percentage of 73.57% which shows a positive response with a rating standard of